Ultra-Processed Food Consumption Among Chilean Preschoolers Is Associated With Diets Promoting Non-communicable Diseases - Araya, C.; Corvalán, C.; Cediel, G.; Taillie, L. S.; Reyes, M. (Frontiers in Nutrition, 2021)
INTRODUCTION: In adults, intake of ultra-processed foods (UPF) has been linked with poor diets and adverse health outcomes. In young children, evidence is scarcer but suggests higher dietary share of UPF. OBJECTIVE: To quantify the intake of UPF and its association with the nutrient composition of the diet in a sample of preschoolers in Santiago, Chile. METHODS: Cross-sectional analysis of dietary data (24-hours-recalls) from 960 preschoolers. Foods were categorized according to the extent and purpose of processing (NOVA classification) and participants classified in quintiles of UPF intake. We explored the associations between UPF intake (% of the total energy) and intake of nutrients of concern for non-communicable diseases development (carbohydrates, total sugars, fats, and sodium), and nutrients for promotion (proteins, polyunsaturated fats, iron, calcium, zinc, vitamins A, D, C, and B12, folate and fiber) using multivariate regression after controlling for covariates. RESULTS: UPF constituted 49% of the total energy intake. Preschoolers with higher intake consumed more energy, saturated and monounsaturated fats, carbohydrates, total sugars, and vitamin D, compared to preschoolers in the lowest quintile of UPF intake. Contrastingly, UPF intake was negatively associated with the consumption of proteins, polyunsaturated fats, fiber, zinc, a vitamin A, and sodium (p<0.05). CONCLUSION: In Chilean preschoolers, UPF was the primary source of energy intake. The dietary share of UPF was associated with the nutrient composition of the diet. Improving children’s diet should consider not only promoting healthy foods consumption but also limiting UPF consumption.